NRF2-Dependent Placental Effects Vary by Sex and Dose following Gestational Exposure to Ultrafine Particles - Jonathan C. Behlen; Carmen H. Lau; Drew Pendleton; Yixin Li; Aline Rodrigues Hoffmann; Michael C. Golding; Renyi Zhang; Natalie M. Johnson (MDPI AG, 2022)
Exposure to ultrafine particles (UFPs, PM0.1) during pregnancy triggers placental oxidative stress and inflammation, similar to fine PM (PM2.5). The Nrf2 gene encodes a redox-sensitive transcription factor that is a major regulator of antioxidant and anti-inflammatory responses. Disruption of NRF2 is known to substantially enhance PM2.5-driven oxidant and inflammatory responses; however, specific responses to UFP exposure, especially during critical windows of susceptibility such as pregnancy, are not fully characterized; To investigate the role of NRF2 in regulating maternal antioxidant defenses and placental responses to UFP exposure, wildtype (WT) and Nrf2−/− pregnant mice were exposed to either low dose (LD, 100 µg/m3) or high dose (HD, 500 µg/m3) UFP mixture or filtered air (FA, control) throughout gestation; Nrf2−/− HD-exposed female offspring exhibited significantly reduced fetal and placental weights. Placental morphology changes appeared most pronounced in Nrf2−/− LD-exposed offspring of both sexes. Glutathione (GSH) redox analysis revealed significant increases in the GSH/GSSG ratio (reduced/oxidized) in WT female placental tissue exposed to HD in comparison with Nrf2−/− HD-exposed mice. The expression of inflammatory cytokine genes (Il1β, Tnfα) was significantly increased in Nrf2−/− placentas from male and female offspring across all exposure groups. Genes related to bile acid metabolism and transport were differentially altered in Nrf2−/− mice across sex and exposure groups. Notably, the group with the most marked phenotypic effects (Nrf2−/− HD-exposed females) corresponded to significantly higher placental Apoa1 and Apob expression suggesting a link between placental lipid transport and NRF2 in response to high dose UFP exposure; Disruption of NRF2 exacerbates adverse developmental outcomes in response to high dose UFP exposure in female offspring. Morphological effects in placenta from male and female offspring exposed to low dose UFPs also signify the importance of NRF2 in maternal-fetal response to UFPs.